Inorganic magnesium salt electrolyte for rechargeable magnesium battery as well as preparation method and application of inorganic magnesium salt electrolyte

By using inorganic magnesium salts, organic ether solvents and organophosphorus molecules in magnesium battery electrolyte, the problems of poor solubility and low oxidation stability of magnesium battery electrolyte are solved, and efficient magnesium ion dissolution-deposition process and electrochemical performance are achieved.

CN119905658AActive Publication Date: 2025-04-29JIANGSU UNIV OF SCI & TECH

Patent Information

Application Number
CN202510249686.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-04
Publication Date
2025-04-29
Estimated Expiration
2045-03-04

AI Technical Summary

Technical Problem

The existing magnesium battery electrolyte has poor solubility, low oxidation stability, poor performance withstand high currents, complex preparation process and high cost, which hinders the development of rechargeable magnesium ion batteries.

Method used

Inorganic magnesium salts (such as magnesium chloride) are used as electrolyte salts, combined with organic ether solvents and organic phosphorus molecules as electrolyte additives, so as to improve the solubility and conductivity of magnesium ions through interaction, reduce the overpotential, and form a stable solid electrolyte conductive layer.

Benefits of technology

It significantly improves the electrochemical performance of magnesium batteries, enhances the dissolution-deposition efficiency of magnesium ions, reduces the electrochemical polarization of the electrolyte, improves the reversibility and oxidation stability of the battery, and reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119905658A_ABST
    Figure CN119905658A_ABST
Patent Text Reader

Abstract

The invention discloses a rechargeable magnesium battery inorganic magnesium salt electrolyte and a preparation method and application thereof, and belongs to the technical field of new energy battery preparation. The inorganic magnesium salt electrolyte of the rechargeable magnesium battery comprises an electrolyte salt inorganic magnesium salt, an organic ether solvent and an electrolyte additive organic phosphorus molecule. The organic phosphorus molecules with high dielectric constant are introduced into the inorganic magnesium salt electrolyte, the solvation structure of magnesium ions in the electrolyte and the dissolvability of the electrolyte are optimized and regulated, a stable magnesium ion solid electrolyte conducting layer is formed on the surface of magnesium metal, the conductivity of the magnesium ions is improved, and the service life of the electrolyte is prolonged. And the side reaction between the magnesium negative electrode and the electrolyte is reduced. Meanwhile, the electrochemical polarization energy barrier of the electrolyte is reduced, and the reversibility and oxidation stability of the rechargeable magnesium battery are improved. The electrolyte can be prepared only by adding the single inorganic magnesium salt and the organophosphorus additive into the ether solvent and stirring, additional additives and dewatering agents are not needed, the preparation method is simple, and large-scale production is easy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of new energy battery preparation, and in particular to an inorganic magnesium salt electrolyte for a rechargeable magnesium battery and a preparation method and application thereof. Background Art

[0002] Rechargeable lithium-ion batteries have revolutionized the mobile device industry and are gaining increasing attention in the development of electric vehicles and grid storage applications. However, due to the scarcity and high cost of lithium resources, people need to explore more sustainable battery materials. Rechargeable magnesium batteries stand out because magnesium metal acts as the negative electrode and rarely produces dendrites on the surface during battery charging and discharging. In addition, magnesium metal has a low reduction potential (-2.37 V vs. standard hydrogen electrode) and exhibits a high theoretical mass specific capacity (2205 mAh g -1 ) and volumetric capacity (3833 mAh cm -3 ), which is more abundant in the earth's crust (1.94% magnesium and 0.002% lithium). 2+ Replace monovalent ions (Li + 、Na + ) can realize rechargeable batteries with high energy density.

[0003] However, the lack of suitable electrolytes remains a key challenge in building high energy density rechargeable magnesium batteries. 2+ The transport medium not only determines the compatibility with the electrode, but also the electrochemical, thermodynamic and safety stability of the battery energy storage system. In traditional magnesium battery electrolytes, the Mg surface is easily severely passivated, which hinders the dissolution-deposition process of magnesium ions, resulting in slow kinetics and ultra-high overpotential. There are few traditional electrolytes that meet the wide electrochemical window and can reversibly dissolve and deposit magnesium metal.

[0004] Taken together, these challenges have greatly hindered the development of rechargeable Mg-ion batteries. Summary of the invention

[0005] Purpose of the invention: In order to solve the problems of poor solubility, low oxidation stability, poor high current resistance, complex preparation process and high cost of existing magnesium battery electrolytes, the first purpose of the present invention is to provide an inorganic magnesium salt electrolyte for a rechargeable magnesium battery with high ionic conductivity and high magnesium metal dissolution-deposition efficiency. The second purpose of the present invention is to provide a method for preparing the above-mentioned inorganic magnesium salt electrolyte for a rechargeable magnesium battery. The third purpose of the present invention is to provide an application of the above-mentioned inorganic magnesium salt electrolyte for a rechargeable magnesium battery.

[0006] Technical solution: The inorganic magnesium salt electrolyte for the rechargeable magnesium battery of the present invention comprises an electrolyte salt, an organic ether solvent and an electrolyte additive; the electrolyte salt is an inorganic magnesium salt, the electrolyte additive is an organic phosphorus molecule, and the volume fraction of the organic phosphorus molecule in the electrolyte is 5-40%, preferably 20-40%.

[0007] Furthermore, the inorganic magnesium salt is magnesium chloride, which is mainly used as a source of magnesium ions in the electrolyte. Compared with other common magnesium salts, magnesium chloride has higher conductivity and better magnesium metal dissolution and deposition efficiency. It is also low in cost, simple in synthesis steps, and not easily affected by trace amounts of moisture, making it an ideal electrolyte salt.

[0008] Furthermore, the organic ether solvent is one or more of tetrahydrofuran, ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, 1,3-dioxolane and 1,4-dioxane, preferably tetrahydrofuran or ethylene glycol dimethyl ether.

[0009] Furthermore, the organic phosphorus molecule is at least one of trimethyl phosphate, triethyl phosphate, dibutyl phosphate, and trimethyl phosphite, preferably trimethyl phosphate or triethyl phosphate.

[0010] Furthermore, the molar concentration of the electrolyte salt in the electrolyte is 0.1-1.0 mol / L, preferably 0.25-0.5 mol / L.

[0011] The present invention provides a method for preparing the inorganic magnesium salt electrolyte for the rechargeable magnesium battery, comprising the following steps:

[0012] (1) adding an inorganic magnesium salt to an organic ether solvent and stirring to dissolve and disperse the inorganic magnesium salt to obtain a reaction solution;

[0013] (2) Adding an electrolyte additive to the above reaction solution and continuing to stir until it is fully mixed, an inorganic magnesium salt electrolyte for a rechargeable magnesium battery is obtained.

[0014] Furthermore, step (1) and step (2) are carried out in an argon glove box with water and oxygen contents both lower than 0.1 ppm; the organic ether solvent and electrolyte additive are pre-dried with molecular sieves; and the stirring conditions are: stirring temperature of 40-90°C, stirring speed of 300-1000 r / min, and stirring time of 10-20 min.

[0015] The invention provides application of inorganic magnesium salt electrolyte of rechargeable magnesium battery in symmetrical battery and asymmetrical battery in magnesium ion battery.

[0016] Furthermore, the symmetrical battery includes a positive electrode material, a negative electrode material, a diaphragm and a rechargeable magnesium battery composite electrolyte, wherein the positive electrode material is metallic magnesium or a magnesium alloy; the asymmetric battery includes a positive electrode material, a negative electrode material, a diaphragm and a rechargeable magnesium battery electrolyte, wherein the positive electrode material is aluminum, copper, molybdenum, stainless steel, titanium or zinc.

[0017] Furthermore, the negative electrode materials of the symmetrical battery and the asymmetrical battery are both metal magnesium or magnesium alloy, and the diaphragms are at least one of glass fiber diaphragms, polyethylene films, polypropylene films or polymer composite films.

[0018] Principle of the invention: In the inorganic magnesium salt electrolyte of the rechargeable magnesium battery of the present invention, the following interactions exist:

[0019] 1. Organic phosphorus molecules as electrolyte additives interact with ether solvents: Organic phosphorus molecules interact strongly with ether solvents at the molecular level. Since organic phosphorus molecules have a high dielectric constant, they can form a synergistic effect with the polar part of the solvent molecules, thereby changing the solvation structure of magnesium ions. This effect helps to increase the solubility of magnesium ions in the solvent, making it easier for them to migrate to the electrode surface and improve the conductivity of the electrolyte. Especially under high load current conditions, the increase in electrolyte conductivity will reduce the overpotential, thereby improving battery performance.

[0020] 2. Interaction between organic phosphorus molecules and inorganic magnesium salts as electrolyte additives: Inorganic magnesium salts usually form dimeric cationic complexes (such as [Mg2(μ-Cl)3·solvent]+) in solvents, which are active substances in electrolytes. Under the action of organic phosphorus molecules, the stability of these complexes can be adjusted, thereby changing the solvation structure of magnesium ions in the electrolyte and promoting the dissolution of magnesium ions and electrode deposition processes.

[0021] 3. Interaction between organic phosphorus molecules in electrolyte additives and electrode surfaces: Organic phosphorus molecules interact with the surface of the magnesium metal negative electrode during the operation of the battery, promoting the formation of a stable solid electrolyte conductive layer on the electrode surface. This layer not only helps to improve the deposition efficiency of magnesium ions, but also reduces the adverse reactions between the electrolyte and the metal negative electrode (such as the formation of a passivation film), thereby maintaining the efficient cycle performance of the battery. This solid electrolyte conductive layer plays an important buffering role in the battery charging and discharging process, slowing down the side reactions between the electrolyte and the negative electrode, and improving the overall stability and oxidation stability of the battery.

[0022] 4. The role of organic phosphorus molecules as electrolyte additives and electrolyte electrochemical polarization: The addition of organic phosphorus molecules reduces the electrochemical polarization energy barrier of the electrolyte during the battery charging and discharging process. This role helps to improve the deposition-dissolution efficiency of magnesium metal and reduce the overpotential of the battery, especially at high current density.

[0023] In summary, the role of the organophosphorus molecules in the electrolyte of the present invention is not limited to improving the conductivity of the electrolyte and reducing the overpotential, but also includes interactions with other solvents (such as ether solvents) to enhance the stability and electrochemical performance of the electrolyte. Through this interaction, the organophosphorus molecules help improve the solubility of magnesium ions, promote the deposition-dissolution process of magnesium metal, reduce the side reactions of the electrolyte and the formation of passivation films, thereby providing a guarantee for the high performance and long-term stability of the battery.

[0024] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages: the present invention uses magnesium chloride as a single magnesium salt and organic phosphorus molecules as a single component additive to dissolve and prepare an electrolyte, does not require additional additives and dehydrating agents, solves the solubility problem of magnesium chloride in ether solvents, greatly reduces the production process cost, is easy to mass produce, and at the same time improves the electrochemical performance, reduces the electrochemical polarization of the electrolyte itself, thereby improving the reversibility and oxidation stability of the rechargeable magnesium battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 The photographs are of the electrolytes prepared in Examples 1 to 10 and Comparative Examples 1 to 3;

[0026] Figure 2 This is a comparison chart of the conductivity of the electrolytes prepared in Examples 1 to 5 and Comparative Example 2;

[0027] Figure 3 The charge and discharge curves of the electrolytes prepared in Examples 1 to 5 and Comparative Example 2 in a Mg||Mg symmetric battery, with a current density of 0.1 mA cm -2 , with an area capacity of 0.05 mAh cm -2 ;

[0028] Figure 4 The charge and discharge curves of the electrolytes prepared in Examples 4, 6 and 8 in Mg||Mg symmetrical cells (wherein the current density in Example 4 is 0.5 mA cm -2 , with an area capacity of 0.25 mAh cm -2 , the current density of Examples 6-8 is 0.1 mA cm -2 , with an area capacity of 0.05 mAh cm -2 );

[0029] Figure 5 The rate performance curves of the electrolytes prepared in Examples 1-5 and 7-8 in Mg||Mg symmetric cells at different current densities. The current density test range is 0.05 mA cm -2 Up to 6mA cm -2, with an area capacity of 0.2 mAh cm -2 ;

[0030] Figure 6 The charge and discharge curves of the electrolytes prepared in Examples 9-10 and Comparative Example 3 in a Mg||Mg symmetrical battery, with a current density of 0.1 mA cm -2 , with an area capacity of 0.05 mAh cm -2 ;

[0031] Figure 7 The rate performance curves of the electrolytes prepared in Examples 9-10 and Comparative Example 3 in Mg||Mg symmetric cells at different current densities are shown in the figure. The current density test range is 0.05 mA cm -2 Up to 6mA cm -2 , with an area capacity of 0.2 mAh cm -2 ;

[0032] Figure 8 The electrochemical impedance spectroscopy (EIS) diagrams of the electrolytes prepared in Examples 1 to 5 before and after cycling in a Mg||Mg symmetric battery, with a test range of 10 6 Hz to 10 -2 Hz, amplitude 5mV;

[0033] Fig. 9 Linear sweep voltammetry (LSV) diagrams of asymmetric cells composed of different research electrodes and magnesium electrodes using the electrolytes prepared in Examples 1 to 5. The voltage sweep range is from open circuit voltage (OCV) to 6.5 V, and the sweep rate is 5 mV s -1 ;

[0034] Fig.10 The charge-discharge curves and coulomb efficiency diagram of the electrolyte prepared in Example 4 in an asymmetric battery composed of different research electrodes (SS, Ti) and magnesium electrodes, with a current density of 0.05 mA cm -2 , with an area capacity of 0.025 mAh cm -2 ;

[0035] Fig.11 X-ray diffraction (XRD) patterns of the electrolytes prepared in Examples 1 to 5 after cycling in a Mg||Mg symmetric battery;

[0036] Fig.12 Scanning electron microscope (SEM) images of the electrolytes prepared in Examples 1 to 5 after magnesium metal dissolution / deposition electrochemical testing (wherein a is Example 1, b is Example 2, c is Example 3, d is Example 4, and e is Example 5);

[0037] Fig.13Fourier transform infrared (FTIR) spectra of the electrolytes prepared in Example 4, Example 10, and Comparative Example 2 (including infrared spectra of each single solvent (THF, DME, TEP)). DETAILED DESCRIPTION

[0038] The present invention is further described below in conjunction with specific embodiments and drawings.

[0039] In the following examples, the battery performance tests were performed using a Blue Electric battery test system and a Chenhua electrochemical workstation, and the physical properties were characterized using a scanning electron microscope and an X-ray diffractometer. In order to test the electrochemical properties of the electrolyte, Mg||Mg symmetric cells and asymmetric cells (including Mg||Al, Mg||Cu, Mg||Mo, Mg||SS, Mg||Ti) were used, respectively, using the electrolytes prepared in the following examples, the diaphragm was glass fiber, assembled into CR2032 button cells, and magnesium metal dissolution / deposition, electrochemical impedance spectroscopy, linear sweep voltammetry and other tests were performed.

[0040] Example 1: The inorganic magnesium salt electrolyte for a rechargeable magnesium battery provided in this example includes an electrolyte salt, magnesium chloride, an organic solvent, ethylene glycol dimethyl ether, and an electrolyte additive, triethyl phosphate. The volume ratio of ethylene glycol dimethyl ether to triethyl phosphate is 95:5, and the molar concentration of magnesium chloride in the electrolyte is 0.25 mol / L.

[0041] The preparation method of the above-mentioned electrolyte includes the following steps: in an argon glove box with water and oxygen contents lower than 0.1ppm, 0.119g of anhydrous magnesium chloride is weighed and added to 4.75mL of ethylene glycol dimethyl ether solvent, and the temperature is maintained at 45°C with a stirring speed of 600r / min and magnetically stirred for 15 minutes to ensure that the magnesium chloride is evenly dispersed in the ethylene glycol dimethyl ether to obtain a MgCl2-DME blank electrolyte; then, 0.25mL of triethyl phosphate (TEP) is sucked by a pipette and added to the MgCl2-DME blank electrolyte, and the volume ratio of triethyl phosphate to the solvent is controlled to be 5%, and the temperature is maintained at 45°C with a stirring speed of 600r / min and magnetically stirred for 30 minutes. After sufficient reaction, a colorless, clear and transparent composite electrolyte is obtained, i.e., 0.25mol / L (M) MgCl2-DME-5% TEP electrolyte. The electrolyte is added with an appropriate amount before use. The molecular sieve was dried overnight. The moisture content of the electrolyte was tested to be less than 10ppm.

[0042] Example 2: The inorganic magnesium salt electrolyte for a rechargeable magnesium battery provided in this example includes an electrolyte salt, magnesium chloride, an organic solvent, ethylene glycol dimethyl ether, and an electrolyte additive, triethyl phosphate. The volume ratio of ethylene glycol dimethyl ether to triethyl phosphate is 90:10, and the molar concentration of magnesium chloride in the electrolyte is 0.25 mol / L.

[0043] The preparation method of the above-mentioned electrolyte includes the following steps: in an argon glove box with water and oxygen contents lower than 0.1ppm, 0.119g of anhydrous magnesium chloride is weighed and added to 4.5mL of ethylene glycol dimethyl ether solvent, and the temperature is maintained at 45°C with a stirring speed of 600r / min and magnetically stirred for 15 minutes to ensure that the magnesium chloride is evenly dispersed in the ethylene glycol dimethyl ether to obtain a MgCl2-DME blank electrolyte; then, 0.5mL of triethyl phosphate (TEP) is sucked by a pipette and added to the MgCl2-DME blank electrolyte, and the volume ratio of triethyl phosphate to the solvent is controlled to be 10%, and the temperature is maintained at 45°C with a stirring speed of 600r / min and magnetically stirred for 30 minutes. After sufficient reaction, a colorless, clear and transparent composite electrolyte is obtained, i.e., 0.25mol / L (M) MgCl2-DME-10% TEP electrolyte. The electrolyte is added with an appropriate amount before use. The molecular sieve was dried overnight. The moisture content of the electrolyte was tested to be less than 10ppm.

[0044] Example 3: The inorganic magnesium salt electrolyte for a rechargeable magnesium battery provided in this example includes an electrolyte salt, magnesium chloride, an organic solvent, ethylene glycol dimethyl ether, and an electrolyte additive, triethyl phosphate. The volume ratio of ethylene glycol dimethyl ether to triethyl phosphate is 80:20, and the molar concentration of magnesium chloride in the electrolyte is 0.25 mol / L.

[0045] The preparation method of the above-mentioned electrolyte includes the following steps: in an argon glove box with water and oxygen contents lower than 0.1ppm, 0.119g of anhydrous magnesium chloride is weighed and added to 4mL of ethylene glycol dimethyl ether solvent, and the temperature is maintained at 45°C with a stirring speed of 600r / min and magnetically stirred for 15 minutes to ensure that the magnesium chloride is evenly dispersed in the ethylene glycol dimethyl ether to obtain a MgCl2-DME blank electrolyte; then, 1mL of triethyl phosphate (TEP) is drawn with a pipette and added to the MgCl2-DME blank electrolyte, and the volume ratio of triethyl phosphate to the solvent is controlled to be 20%, and the temperature is maintained at 45°C with a stirring speed of 600r / min and magnetically stirred for 30 minutes. After sufficient reaction, a colorless, clear and transparent composite electrolyte is obtained, i.e., 0.25mol / L(M)MgCl2-DME-20% TEP electrolyte. The electrolyte is added with an appropriate amount before use. The molecular sieve was dried overnight. The moisture content of the electrolyte was tested to be less than 10ppm.

[0046] Example 4: The inorganic magnesium salt electrolyte for a rechargeable magnesium battery provided in this example includes an electrolyte salt, magnesium chloride, an organic solvent, ethylene glycol dimethyl ether, and an electrolyte additive, triethyl phosphate. The volume ratio of ethylene glycol dimethyl ether to triethyl phosphate is 70:30, and the molar concentration of magnesium chloride in the electrolyte is 0.25 mol / L.

[0047] The preparation method of the above-mentioned electrolyte includes the following steps: in an argon glove box with water and oxygen contents lower than 0.1ppm, 0.119g of anhydrous magnesium chloride is weighed and added to 3.5mL of ethylene glycol dimethyl ether solvent, and the temperature is maintained at 45°C with a stirring speed of 600r / min and magnetically stirred for 15 minutes to ensure that the magnesium chloride is evenly dispersed in the ethylene glycol dimethyl ether to obtain a MgCl2-DME blank electrolyte; then 1.5mL of triethyl phosphate (TEP) is sucked by a pipette and added to the MgCl2-DME blank electrolyte, and the volume ratio of triethyl phosphate to the solvent is controlled to be 30%, and the temperature is maintained at 45°C with a stirring speed of 600r / min and magnetically stirred for 30 minutes. After sufficient reaction, a colorless, clear and transparent composite electrolyte is obtained, i.e., 0.25mol / L (M) MgCl2-DME-30% TEP electrolyte. The electrolyte is added with an appropriate amount before use. The molecular sieve was dried overnight. The moisture content of the electrolyte was tested to be less than 10ppm.

[0048] Example 5: The inorganic magnesium salt electrolyte for a rechargeable magnesium battery provided in this embodiment includes an electrolyte salt of magnesium chloride, an organic solvent of ethylene glycol dimethyl ether, and an electrolyte additive of triethyl phosphate, the volume ratio of ethylene glycol dimethyl ether to triethyl phosphate is 60:40, and the molar concentration of magnesium chloride in the electrolyte is 0.25 mol / L.

[0049] The preparation method of the above-mentioned electrolyte includes the following steps: in an argon glove box with water and oxygen contents lower than 0.1ppm, 0.119g of anhydrous magnesium chloride is weighed and added to 3mL of ethylene glycol dimethyl ether solvent, and the temperature is maintained at 45°C with a stirring speed of 600r / min and magnetically stirred for 15 minutes to ensure that the magnesium chloride is evenly dispersed in the ethylene glycol dimethyl ether to obtain a MgCl2-DME blank electrolyte; then 2mL of triethyl phosphate (TEP) is drawn with a pipette and added to the MgCl2-DME blank electrolyte, and the volume ratio of triethyl phosphate to the solvent is controlled to be 40%, and the temperature is maintained at 45°C with a stirring speed of 600r / min and magnetically stirred for 30 minutes. After sufficient reaction, a colorless, clear and transparent composite electrolyte is obtained, i.e., 0.25mol / L(M)MgCl2-DME-40% TEP electrolyte. The electrolyte is added with an appropriate amount before use. The molecular sieve was dried overnight. The moisture content of the electrolyte was tested to be less than 10ppm.

[0050] Example 6: The inorganic magnesium salt electrolyte for a rechargeable magnesium battery provided in this example includes an electrolyte salt, magnesium chloride, an organic solvent, ethylene glycol dimethyl ether, and an electrolyte additive, trimethyl phosphate. The volume ratio of ethylene glycol dimethyl ether to trimethyl phosphate is 70:30, and the molar concentration of magnesium chloride in the electrolyte is 0.25 mol / L.

[0051] The preparation method of the above-mentioned electrolyte includes the following steps: in an argon glove box with water and oxygen contents lower than 0.1ppm, 0.119g of anhydrous magnesium chloride is weighed and added to 3.5mL of ethylene glycol dimethyl ether solvent, and the temperature is maintained at 45°C with a stirring speed of 600r / min and magnetically stirred for 15 minutes to ensure that the magnesium chloride is evenly dispersed in the ethylene glycol dimethyl ether to obtain a MgCl2-DME blank electrolyte; then, 1.5mL of trimethyl phosphate (TMP) is sucked by a pipette and added to the MgCl2-DME blank electrolyte, and the volume ratio of trimethyl phosphate to the solvent is controlled to be 30%, and the temperature is maintained at 45°C with a stirring speed of 600r / min and magnetically stirred for 30 minutes. After sufficient reaction, a colorless, clear and transparent composite electrolyte is obtained, i.e., 0.25mol / L(M)MgCl2-DME-30%TMP electrolyte. The electrolyte is added with an appropriate amount before use. The molecular sieve was dried overnight. The moisture content of the electrolyte was tested to be less than 10ppm.

[0052] Example 7: The inorganic magnesium salt electrolyte for a rechargeable magnesium battery provided in this example includes an electrolyte salt, magnesium chloride, an organic solvent, ethylene glycol dimethyl ether, and an electrolyte additive, triethyl phosphate. The volume ratio of ethylene glycol dimethyl ether to triethyl phosphate is 80:20, and the molar concentration of magnesium chloride in the electrolyte is 0.5 mol / L.

[0053] The preparation method of the above-mentioned electrolyte includes the following steps: in an argon glove box with water and oxygen contents lower than 0.1ppm, 0.238g of anhydrous magnesium chloride is weighed and added to 4mL of ethylene glycol dimethyl ether solvent, and the temperature is maintained at 45°C with a stirring speed of 600r / min and magnetically stirred for 15 minutes to ensure that the magnesium chloride is evenly dispersed in the ethylene glycol dimethyl ether to obtain a MgCl2-DME blank electrolyte; then, 1mL of triethyl phosphate (TEP) is drawn with a pipette and added to the MgCl2-DME blank electrolyte, and the volume ratio of triethyl phosphate to the solvent is controlled to be 20%, and the temperature is maintained at 45°C with a stirring speed of 600r / min and magnetically stirred for 30 minutes. After sufficient reaction, a colorless, clear and transparent composite electrolyte is obtained, i.e., 0.5mol / L(M)MgCl2-DME-20% TEP electrolyte. The electrolyte is added with an appropriate amount before use. The molecular sieve was dried overnight. The moisture content of the electrolyte was tested to be less than 10ppm.

[0054] Example 8: The inorganic magnesium salt electrolyte for a rechargeable magnesium battery provided in this example includes an electrolyte salt, magnesium chloride, an organic solvent, ethylene glycol dimethyl ether, and an electrolyte additive, triethyl phosphate. The volume ratio of ethylene glycol dimethyl ether to triethyl phosphate is 70:30, and the molar concentration of magnesium chloride in the electrolyte is 0.5 mol / L.

[0055] The preparation method of the above-mentioned electrolyte includes the following steps: in an argon glove box with water and oxygen contents lower than 0.1ppm, 0.238g of anhydrous magnesium chloride is weighed and added to 3.5mL of ethylene glycol dimethyl ether solvent, and the temperature is maintained at 45°C with a stirring speed of 600r / min and magnetically stirred for 15 minutes to ensure that the magnesium chloride is evenly dispersed in the ethylene glycol dimethyl ether to obtain a MgCl2-DME blank electrolyte; then 1.5mL of triethyl phosphate (TEP) is sucked by a pipette and added to the MgCl2-DME blank electrolyte, and the volume ratio of triethyl phosphate to the solvent is controlled to be 30%, and the temperature is maintained at 45°C with a stirring speed of 600r / min and magnetically stirred for 30 minutes. After sufficient reaction, a colorless, clear and transparent composite electrolyte is obtained, i.e., 0.5mol / L (M) MgCl2-DME-30% TEP electrolyte. The electrolyte is added with an appropriate amount before use. The molecular sieve was dried overnight. The moisture content of the electrolyte was tested to be less than 10ppm.

[0056] Example 9: The inorganic magnesium salt electrolyte for a rechargeable magnesium battery provided in this example includes an electrolyte salt, magnesium chloride, an organic solvent, tetrahydrofuran, and an electrolyte additive, triethyl phosphate. The volume ratio of tetrahydrofuran to triethyl phosphate is 80:20, and the molar concentration of magnesium chloride in the electrolyte is 0.25 mol / L.

[0057] The preparation method of the above-mentioned electrolyte includes the following steps: in an argon glove box with water and oxygen contents less than 0.1ppm, 0.119g of anhydrous magnesium chloride is weighed and added to 4mL of tetrahydrofuran solvent, and the temperature is maintained at 45°C with a stirring speed of 600r / min and magnetic stirring is performed for 15 minutes to ensure that the magnesium chloride is evenly dispersed in tetrahydrofuran to obtain a MgCl2-THF blank electrolyte; then 1mL of triethyl phosphate (TEP) is drawn with a pipette and added to the MgCl2-THF blank electrolyte, and the volume ratio of triethyl phosphate to the solvent is controlled to be 20%, and the temperature is maintained at 45°C with a stirring speed of 600r / min and magnetic stirring is performed for 30 minutes. After sufficient reaction, a colorless, clear and transparent composite electrolyte is obtained, namely 0.25mol / L(M)MgCl2-THF-20% TEP electrolyte. The electrolyte is added with an appropriate amount before use. The molecular sieve was dried overnight. The moisture content of the electrolyte was tested to be less than 10ppm.

[0058] Example 10: The inorganic magnesium salt electrolyte for a rechargeable magnesium battery provided in this example includes an electrolyte salt, magnesium chloride, an organic solvent, tetrahydrofuran, and an electrolyte additive, triethyl phosphate. The volume ratio of tetrahydrofuran to triethyl phosphate is 70:30, and the molar concentration of magnesium chloride in the electrolyte is 0.25 mol / L.

[0059] The preparation method of the above-mentioned electrolyte includes the following steps: in an argon glove box with water and oxygen contents less than 0.1ppm, 0.119g of anhydrous magnesium chloride is weighed and added to 3.5mL of tetrahydrofuran solvent, and the temperature is maintained at 45°C with a stirring speed of 600r / min and magnetically stirred for 15 minutes to ensure that the magnesium chloride is evenly dispersed in tetrahydrofuran to obtain a MgCl2-THF blank electrolyte; then 1.5mL of triethyl phosphate (TEP) is sucked with a pipette and added to the MgCl2-THF blank electrolyte, and the volume ratio of triethyl phosphate to the solvent is controlled to be 30%, and the temperature is maintained at 45°C with a stirring speed of 600r / min and magnetically stirred for 30 minutes. After sufficient reaction, a colorless, clear and transparent composite electrolyte is obtained, namely 0.25mol / L (M) MgCl2-THF-30% TEP electrolyte. The electrolyte is added with an appropriate amount before use. The molecular sieve was dried overnight. The moisture content of the electrolyte was tested to be less than 10ppm.

[0060] Comparative Example 1: The electrolyte provided in this comparative example is prepared by the following method: in an argon glove box where the water and oxygen contents are both lower than 0.1 ppm, 0.119 g of anhydrous magnesium chloride is weighed and added to 5 mL of ethylene glycol dimethyl ether solvent, and the temperature is maintained at 45°C with a stirring speed of 600 r / min and magnetic stirring is performed for 30 minutes to ensure that the magnesium chloride is evenly dispersed in the ethylene glycol dimethyl ether to form a milky white turbid liquid with suspended particles, to obtain a blank saturated electrolyte of 0.25 mol / L (M) MgCl2-DME.

[0061] Comparative Example 2: The electrolyte provided in this comparative example is prepared by weighing 0.119 g of anhydrous magnesium chloride and adding it to 5 mL of triethyl phosphate (TEP) solvent in an argon glove box with water and oxygen contents both lower than 0.1 ppm, stirring at 600 r / min and maintaining the temperature at 45°C for 30 minutes with magnetic stirring to ensure that the magnesium chloride is evenly dispersed and dissolved in the triethyl phosphate, to obtain a 0.25 mol / L (M) MgCl2-TEP clear and transparent electrolyte. The electrolyte is added with an appropriate amount of The molecular sieve was dried overnight. The moisture content of the electrolyte was tested to be less than 10ppm.

[0062] Comparative Example 3: The electrolyte provided in this comparative example is prepared by weighing 0.119 g of anhydrous magnesium chloride and adding it to 5 mL of tetrahydrofuran (THF) solvent in an argon glove box with water and oxygen contents both lower than 0.1 ppm, stirring at 600 r / min and maintaining the temperature at 45°C with magnetic stirring for 60 minutes to ensure that the magnesium chloride is evenly dispersed and dissolved in tetrahydrofuran, and obtaining a 0.25 mol / L (M) MgCl2-THF clear and transparent blank electrolyte. Before use, add an appropriate amount of the electrolyte The molecular sieve was dried overnight. The moisture content of the electrolyte was tested to be less than 10ppm.

[0063] The electrolytes prepared in Examples 1 to 10 and Comparative Examples 1 to 3 were characterized and tested for performance. Figure 1-Figure 13 .

[0064] Figure 1 Photo images of the electrolyte prepared by Example 1-Example 10 and Comparative Example 1-Comparative Example 3 (where a is Comparative Example 1, b is Example 1, c is Example 2, d is Example 3, e is Example 4, f is Example 5, g is Comparative Example 2, h is Example 6, i is Example 7, j is Example 8, k is Comparative Example 3, l is Example 9, and m is Example 10). The test results show that inorganic magnesium chloride salt can be dissolved in cyclic ether solvent tetrahydrofuran (THF), but adding different concentrations of triethyl phosphate can accelerate the dissolution and obtain a clear electrolyte faster; but inorganic magnesium chloride salt has poor solubility in chain ether solvent ethylene glycol dimethyl ether (DME), and the solubility problem of inorganic magnesium chloride salt in chain ether solvent can be solved by adding different concentrations of triethyl phosphate (TEP) or trimethyl phosphate (TMP). Due to the poor solubility of anhydrous magnesium chloride in a single ether solvent, no much research was conducted on Comparative Example 1 in the future.

[0065] Figure 2 The conductivity comparison diagram of the electrolyte prepared in Example 1 to Example 5 and Comparative Example 2. The test results show that the conductivity of the electrolyte added with different concentrations of triethyl phosphate in 0.25M (mol / L) MgCl2-DME electrolyte continues to increase until it reaches the 30% inflection point and then begins to decrease, indicating that 30% concentration of triethyl phosphate in the MgCl2-DME electrolyte is the optimal concentration ratio, and the addition of 30% triethyl phosphate greatly promotes the migration kinetics of magnesium ions.

[0066] Figure 3 The charge-discharge curves and cycle stability of the magnesium negative electrode prepared in Examples 1 to 5 and Comparative Example 2 in the corresponding electrolytes (where a is Example 1, b is Example 2, c is Example 3, d is Example 4, e is Example 5, and f is Comparative Example 2). The test results show the charge-discharge performance of the electrolyte with different concentrations of triethyl phosphate added to the 0.25M (mol / L) MgCl2-DME electrolyte in the Mg||Mg symmetrical battery, and the constant current charge-discharge current density is set to 0.1mAcm -2 , constant capacity 0.05 mAh cm -2The addition of triethyl phosphate significantly reduced the overpotential of magnesium metal dissolution / deposition, greatly promoting the interfacial charge transfer kinetics, indicating that this type of electrolyte has excellent electrochemical performance of magnesium metal negative electrode. Since the electrochemical performance of inorganic magnesium chloride in 100% triethyl phosphate solvent is poor, no further in-depth research was conducted.

[0067] Figure 4 The charge-discharge curves and cycle stability of the magnesium negative electrode prepared in Examples 4, 6-8 in the corresponding electrolytes (a is Example 4, b is Example 6, c is Example 7, and d is Example 8). The test results show the charge-discharge performance of the electrolyte in which 30% triethyl phosphate is added to the 0.25M (mol / L) MgCl2-DME electrolyte in the Mg||Mg symmetrical battery, and the constant current charge-discharge current density is set to 0.5mAcm -2 , constant capacity 0.25 mAh cm -2 Even if the current density is increased five times, the symmetrical battery has a low overpotential (less than 0.5V) and can maintain a cycle performance of more than 800h, indicating that this concentration has a more excellent electrochemical performance of the magnesium metal negative electrode; it also shows the charge and discharge performance of the electrolyte with 30% concentration of trimethyl phosphate added to the 0.25M (mol / L) MgCl2-DME electrolyte in the Mg||Mg symmetrical battery, and the constant current charge and discharge current density is set to 0.1mAcm -2 , constant capacity 0.05 mAh cm -2 Even if triethyl phosphate is replaced by trimethyl phosphate, the symmetrical cell still has a lower overpotential, indicating that the high dielectric constant organic phosphorus molecules improve the solubility of inorganic magnesium salts in DME while also improving the interfacial charge transfer kinetics; Example 7-Example 8 shows the charge and discharge performance of 0.5M (mol / L) MgCl2-DME electrolyte with different concentrations of triethyl phosphate added in the Mg||Mg symmetrical cell, and the constant current charge and discharge current density is set to 0.1mAcm -2 , constant capacity 0.05 mAh cm -2 When the main salt concentration is doubled and different concentrations of triethyl phosphate are added, the symmetrical battery still has a low overpotential and can maintain a cycle performance of more than 800h. This shows that this type of electrolyte has excellent electrochemical performance of magnesium metal negative electrode.

[0068] Figure 5The rate polarization performance curves of the electrolytes prepared in Examples 1-5, 7-8 at different current densities in Mg||Mg symmetric batteries (where a is Example 1, b is Example 2, c is Example 3, d is Example 4, e is Example 5, f is Example 7, and g is Example 8), with a constant area capacity of 0.2 mAh cm -2 The addition of triethyl phosphate significantly increased the limit of tolerable current density, even if the current density was increased from 0.05 mA cm -2 Increase to 6mAcm -2 , and can maintain stable magnesium metal dissolution / deposition behavior, indicating that this type of electrolyte has excellent rate performance.

[0069] Figure 6 The charge-discharge curves and cycle stability of the magnesium negative electrode prepared in Examples 9-10 and Comparative Example 3 in the corresponding electrolytes (a is Comparative Example 3, b is Example 9, and c is Example 10). The test results show the charge-discharge performance of the electrolytes with different concentrations of triethyl phosphate added to 0.25M (mol / L) MgCl2-THF electrolyte in the Mg||Mg symmetric battery, and the constant current charge-discharge current density is set to 0.1mA cm -2 , constant capacity 0.05 mAh cm -2 Inorganic magnesium chloride salt can be completely dissolved in THF. After adding different proportions of triethyl phosphate, the dissolution rate can be accelerated, and the polarization potential becomes smaller. The 20% concentration of triethyl phosphate is preferred. Its symmetrical battery has the lowest overpotential and cycles for nearly 1000h, indicating that even if THF is used as a solvent, the triethyl phosphate additive can significantly reduce the overpotential of magnesium metal dissolution / deposition and improve ionic conductivity.

[0070] Figure 7 The rate polarization performance curves of the electrolytes prepared in Example 9-Example 10 and Comparative Example 3 at different current densities in a Mg||Mg symmetric battery (where a is Comparative Example 3, b is Example 9, and c is Example 10), with a constant area capacity of 0.2 mAh cm -2 When tetrahydrofuran was used as the solvent, the addition of triethyl phosphate in different proportions significantly increased the limit of the tolerable current density, even if the current density was increased from 0.05 mA cm -2 Increase to 6 mA cm -2 , and can maintain stable magnesium metal dissolution / deposition behavior, indicating that this type of electrolyte has excellent rate performance. However, compared with the solvent DME, the rate performance is slightly worse.

[0071] Figure 8EIS diagrams of the electrolytes prepared in Examples 1 to 5 before and after cycling in a Mg||Mg symmetric battery (where a is Example 1, b is Example 2, c is Example 3, d is Example 4, and e is Example 5). The test results show that the electrolytes with different concentrations of triethyl phosphate need to be cycled to have very low interfacial transfer resistance. It also shows that the addition of triethyl phosphate can significantly reduce the interfacial transfer resistance, indicating that its excellent charge transfer kinetics requires a small current electrochemical regulation process, and also indicating that this type of electrolyte has excellent electrochemical performance of magnesium metal negative electrodes.

[0072] Fig. 9 LSV diagrams of the electrolytes prepared in Examples 1 to 5 in asymmetric cells (Mg||Al, Mg||Cu, Mg||SS, Mg||Ti, Mg||Mo cells) composed of different research electrodes and magnesium electrodes (a for Example 1, b for Example 2, c for Example 3, d for Example 4, and e for Example 5). The test results show that the voltage range is OCV to 6.5 V, and the scan rate is 5 mV s -1 Under the conditions of , the electrochemical window of the electrolyte in different working electrodes is greater than 2.5 V, indicating that this type of electrolyte has a wide electrochemical window.

[0073] Fig.10 The charge-discharge curves and coulomb efficiency diagrams of the electrolyte prepared in Example 4 in an asymmetric battery composed of different research electrodes (SS, Ti) and a magnesium electrode (Figures a and b correspond to the charge-discharge curves and coulomb efficiency of the SS working electrode, and Figures c and d correspond to the charge-discharge curves and coulomb efficiency of the Ti working electrode). The test results show that at 0.05 mA cm -2 Under current density conditions, reversible dissolution-deposition cycles can be performed on different working electrodes, and the deposition overpotential and dissolution overpotential are low, and the average coulombic efficiency can be maintained at more than 90% for nearly 2100 cycles. These test results show that this type of electrolyte has excellent magnesium metal dissolution / deposition performance.

[0074] Fig.11 XRD diagram of magnesium electrode after the electrolyte prepared in Examples 1 to 5 was cycled in Mg||Mg symmetric battery. The test results show that the magnesium metal negative electrode deposit is mainly composed of elemental magnesium. The characteristic peaks of the XRD image after battery cycling correspond to the magnesium metal PDF card, and the surface phase of the magnesium electrode has no obvious change.

[0075] Fig.12The SEM images of the electrolytes prepared in Examples 1 to 5 after the magnesium metal dissolution / deposition electrochemical test (a is Example 1, b is Example 2, c is Example 3, d is Example 4, and e is Example 5). The test results show that after charging and discharging, the surface of the magnesium electrode presents a uniform and dense magnesium deposit, indicating that this type of electrolyte has excellent electrochemical performance of the magnesium metal negative electrode.

[0076] Fig.13 The FTIR spectra of the electrolytes prepared in Example 4, Example 10 and Comparative Example 2 are shown in Figure 1. The test results show that after adding different concentrations of triethyl phosphate, the electrolytes prepared in Example 4, Example 10 and Comparative Example 2 have a low concentration of 1022 cm -1 The peak at 1260cm -1 The peak at 1106cm is consistent with the characteristic peak of TEP, which corresponds to the COP and P=O bond of TEP respectively. -1 The sharp peak at 1067 cm -1 The sharp peak at corresponds to the COC bond of THF.

Claims

1. An inorganic magnesium salt electrolyte for a rechargeable magnesium battery, characterized in that: The invention comprises electrolyte salt, organic ether solvent and electrolyte additive; the electrolyte salt is inorganic magnesium salt, the electrolyte additive is organic phosphorus molecule, and the volume fraction of the organic phosphorus molecule in the electrolyte is 5-40%.

2. The inorganic magnesium salt electrolyte for rechargeable magnesium batteries according to claim 1, characterized in that: The volume fraction of the organic phosphorus molecules in the electrolyte is 20-40%.

3. The inorganic magnesium salt electrolyte for rechargeable magnesium batteries according to claim 1, characterized in that: The inorganic magnesium salt is magnesium chloride.

4. The inorganic magnesium salt electrolyte for a rechargeable magnesium battery according to claim 1, characterized in that: The organic ether solvent is one or more of tetrahydrofuran, ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, 1,3-dioxolane and 1,4-dioxane.

5. The inorganic magnesium salt electrolyte for rechargeable magnesium battery according to claim 1, characterized in that: The organic phosphorus molecule is at least one of trimethyl phosphate, triethyl phosphate, dibutyl phosphate, and trimethyl phosphite.

6. The inorganic magnesium salt electrolyte for a rechargeable magnesium battery according to claim 1, characterized in that: The molar concentration of the electrolyte salt in the electrolyte is 0.1-1.0 mol / L.

7. The inorganic magnesium salt electrolyte for a rechargeable magnesium battery according to claim 5, characterized in that: The molar concentration of the electrolyte salt in the electrolyte is 0.25-0.5 mol / L.

8. A method for preparing an inorganic magnesium salt electrolyte for a rechargeable magnesium battery according to claim 1, characterized in that: The following steps are involved: (1) adding an inorganic magnesium salt to an organic ether solvent and stirring to dissolve and disperse the inorganic magnesium salt to obtain a reaction solution; (2) Adding an electrolyte additive to the above reaction solution and continuing to stir until it is fully mixed, an inorganic magnesium salt electrolyte for a rechargeable magnesium battery is obtained.

9. The preparation method according to claim 8, characterized in that: Step (1) and step (2) are carried out in an argon glove box with water and oxygen contents both lower than 0.1 ppm; the stirring conditions are: stirring temperature of 40-90° C., stirring speed of 300-1000 r / min, and stirring time of 10-20 min.

10. Use of the inorganic magnesium salt electrolyte for rechargeable magnesium batteries according to claim 1 in symmetrical batteries and asymmetrical batteries in magnesium ion batteries.

Citation Information

Patent Citations

  • Electrochemical device with a magnesium anode and a stable, safe electrolyte compatible with sulfur

    CN103534862A

  • Electrolyte for magnesium ion battery, preparation method of electrolyte and magnesium ion battery

    CN116454388A

  • Electrolyte applied to rechargeable magnesium battery and rechargeable magnesium battery

    CN118281349A

  • Magnesium battery electrolyte containing insoluble additive and application thereof

    CN119542539A

  • High voltage rechargeable magnesium batteries having a non-aqueous electrolyte

    US20130252112A1

Cited By

  • Halogenate and phosphate composite electrolyte for rechargeable magnesium battery and preparation method and application of halide and phosphate composite electrolyte

    CN121584021A